Chemotherapy-Induced Nausea and Vomiting in Breast Cancer Patients: A Multicenter Prospective Observational Study - Xinjuan Huang; Xuying Li; Jinhua Li; Lu Luo; Hongyun Chen; Yan Tan; Tao Wei; Xingfeng Li; Liwen Guo; Jing Cheng (Asia-Pacific Journal of Oncology Nursing, 2021)
Objective: This study aimed to assess the occurrence of chemotherapy-induced nausea and vomiting (CINV) in acute phase (24 h after chemotherapy) and delayed phase (2–5 days after chemotherapy) after standard antiemetic therapy and to explore the risk factors of CINV in the acute and delayed phases. Methods: This prospective and observational study analyzed the data of 400 breast cancer patients scheduled for chemotherapy in two hospitals. The self-report survey was developed to assess the occurrence of CINV and their associated factors. On day 2 and day 6 of chemotherapy, CINV was evaluated by the Multinational Association of Supportive Care in Cancer Antiemetic Tool (MAT). The incidence of acute and delayed CINV was expressed as frequency and percentage. Results: Among 400 patients, 29.8% and 23.5% experienced acute and delayed CINV, respectively. Logistic regression analysis showed that the risk factors associated with acute CINV included pain/insomnia, history of CINV, and highly emetogenic chemotherapy. The history of motion sickness (MS), history of CINV, number of chemotherapy cycles completed, and the incidence of acute CINV were significant risk factors for delayed CINV (all P < 0.05). Conclusions: The results of this study are helpful for nurses to identify high-risk patients with CINV, formulate effective treatment plans, and reduce the incidence of CINV.